2020
DOI: 10.1007/s00432-020-03329-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti-PD-1 antibodies in NSCLC patients with an EGFR mutation and high PD-L1 expression

Abstract: Introduction Several studies have demonstrated that non-small cell lung cancer patients (NSCLCs) harboring epidermal growth factor receptor (EGFR) mutations have poor clinical outcomes in response to treatment with programmed death-1 (PD-1) inhibitors. However, it remains unclear whether EGFR-mutated NSCLCs with a high programmed death-ligand-1 (PD-L1) expression (tumor proportion score ≥ 50%) respond to PD-1 inhibitors. Methods We retrospectively investigated the NSCLCs who had received PD-1 inhibitors betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 20 publications
2
34
2
Order By: Relevance
“…Our data indicate that EGFR mutation status is associated with high TIL density and high PD-1/PD-L1 expression (cluster 1) and with low TIL density and low PD-1/PD-L1 expression (cluster 2). This result is in contrast with previous reports stating that NSCLC patients with EGFR mutations have high PD-L1 expression ( 23 ). We further evaluated the prognostic value of immune cells in gene-mutated patients and wild-type patients, and the results indicate that only CD8 levels relative to FOXP3 levels have prognostic value in a wild-type subgroup of patients ( Supplementary Figures S4A-G ), underlying the crucial prognostic value of the CD8/FOXP3 ratio.…”
Section: Resultscontrasting
confidence: 99%
“…Our data indicate that EGFR mutation status is associated with high TIL density and high PD-1/PD-L1 expression (cluster 1) and with low TIL density and low PD-1/PD-L1 expression (cluster 2). This result is in contrast with previous reports stating that NSCLC patients with EGFR mutations have high PD-L1 expression ( 23 ). We further evaluated the prognostic value of immune cells in gene-mutated patients and wild-type patients, and the results indicate that only CD8 levels relative to FOXP3 levels have prognostic value in a wild-type subgroup of patients ( Supplementary Figures S4A-G ), underlying the crucial prognostic value of the CD8/FOXP3 ratio.…”
Section: Resultscontrasting
confidence: 99%
“…Chemotherapy and immunotherapy could diminish much further the clinical and subclinical tumor by activing anti-tumor immunity. Our patient with EGFR-TKI resistance responded well to IO combination therapy, which was consistent with the previous study ( 5 ). Thus, PD-L1 TPS 50% or higher may function a predictive role in immunotherapy efficacy after the kinase inhibitor resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Patients with a co-occurrence of high PD-L1 (>50%) and EGFR aberrations were disclosed less than 10% in NSCLC ( 4 ). A Japanese retrospective study found PD-1 inhibitors were more beneficial as second-line or later treatment for EGFR-TKI resistant NSCLC patients with high PD-L1 expression (TPS>50%) than patients with low PD-L1 expression ( 5 ). At the time of resistance to gefitinib, we offered the intervening treatment immunity-combined chemo-radiotherapy to our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that the status of PD-L1 expression could not be used to screen out ICI responders in EGFR-mutant NSCLC patients ( 42 ). On the contrary, other studies demonstrated that ICIs can also be used for EGFR-mutant NSCLC patients who have high PD-L1 expression ( 43 ). In cohort 1 (n=111) of the ALTLANTIC study ( 44 ), durvalumab was used as the third or later line treatment for advanced EGFR/ALK-positive NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%